Adsorption Studies of Methylene Blue and Congo Red on The Surface of Citrus aurantium - Rajasekhar, K.K.; Hari Babu, R.; Manasa Veena, B.; Lavanya, G.; Haripriya, P.; Hamsini, K.V. (Asian Journal of Chemistry, 2010)
The adsorption of organic dyes like methylene blue and congo red on Citrus aurantium using batch adsorption process has been investigated. The effect of certain parameters on adsorption has been studied. Applicability of Freundlich adsorption isotherm and Langmuir adsorption isotherm has also been tested.